Physical and mechanical properties of Nano-SiO2-treated loess - Kong, Ran (Frontiers in Earth Science, 2025)
Improving the performance of loess significantly protects it against failure and degradation, and is important for rammed earth and infrastructure constructed with loess materials. The physical and mechanical properties of nano-SiO2-treated loess were tested with different contents and curing days—including unconfined compressive strength (UCS) and splitting tensile strength (STS)—and their corresponding water content, density, and void ratio. I paid close attention to the homogeneity during sample preparation—that is, sample quality—based on the UCS test. I then analyzed their relation to physical and mechanical properties to gain a better understanding. The results show that the UCS test is a valuable method for examining the quality of sample preparation. UCS, STS, and density increased, and the water content and void ratio decreased with increasing content and curing days due to nano-SiO2 addition. The improvement of mechanical strength is related to the ratio of water content to nano-SiO2 content and curing period rather than the physical properties and additive contents of treated loess. These findings reveal that nano-SiO2 can be an effective stabilizing agent for loess improvement, which has important implications for geohazard mitigation and engineering management in the Chinese loess area.